Assessing attentional bias to emotions in adolescent offenders and nonoffenders - Pino, Mariana; Pardo, Victor; Ruiz, Ronald; González, Gabriel; Parra, Mario Alfredo (Frontiers in Psychology, 2023)
Emotional processing is a cognitive function essential for the interaction of humans with their environment and the development of adaptive behaviors. Adolescent offenders (AOs) express difficulty in cognitive processes linked to emotional processing, which is a response consistently observed during the endogenous (i.e., controlled) control of attention. Less remains understood of the extent to which such atypical responses extend beyond controlled attention and influence exogenous mechanisms (i.e., automatic). This study explores this hypothesis using the recently devised emotional Flanker paradigm. It recruited a group of 39 male AOs and 39 nonoffenders from Barranquilla, Colombia. Assessment consists of an emotional Flanker paradigm administered along with traditional neurocognitive and social cognition tasks. The AOs displayed the well-known attentional bias to threat and a relatively atypical response to emotional targets in which they detected emotions, particularly negative ones, faster than did nonoffenders. Frontal lobe functions account for these effects but not sociodemographic variables nor general cognitive abilities. The results are interpreted in light of evidence suggesting that youngsters with high levels of antisocial behaviors (e.g., callous-unemotional traits) present an enhanced orientation toward distressing stimuli, which is explained by lifelong experiences (e.g., histories of abuse). The findings suggest that environmental influences seemingly exist in the development of these traits, but additional research is required to elucidate the role of cognitive and environmental factors in the development of antisocial behavior.